Effectiveness of VATP in terms of knowledge and attitude regarding assistive respiratory home care management - Pandurangan, Hariprasath; Parwanda, Geeta; Emanel, Rajni (Indian Journal of Nursing Sciences, 2024)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is not a single disease but an umbrella term used to describe chronic lung diseases that cause limitations in lung airflow. The more familiar terms 'chronic bronchitis' and 'emphysema' are no longer used but are now included within the COPD diagnosis. COPD is the fourth leading cause of the death worldwide, and it will become the 3 rd leading cause of the disease by 2020. As per the estimation is done by the WHO around 2.74 million deaths occur due to COPD, which is 5% of the total death worldwide. Aim: The present aims at evaluation of the effectiveness of Video-assisted teaching programme in terms of knowledge & attitude regarding assistive respiratory home care management among patients with COPD. Materials and methods: This study was a pre-experimental study conducted among patients with COPD. A total of 30 samples were selected by using non-probability purposive sampling technique. The data were collected by using structured knowledge interview schedule and modified standardized self-efficacy attitude scale. Results: The mean post-test score of knowledge (21.96), attitude (60.10) is higher than mean pretest score of knowledge (17.23), attitude (47.51) among patients with COPD. The Video-assisted teaching was found to be effective in increasing the knowledge and developing a favorable attitude of the COPD Patients. Conclusion: The result of the study reveals that knowledge deficit and less favorable attitude existed regarding assistive respiratory home care management. The VATP was found to be effective in increasing the knowledge and developing a favourable attitude of the COPD Patients.